The Influence of Pension Funds on Corporate Governance - Urs von Arx; Andreas Schäfer (ETH Zurich, CER-ETH - Center of Economic Research, 2007)
Although pension funds have gained importance in the last two decades, their role has not been described in detail by economic models. This paper focusses on the scope of these institutional investors when they are not satisfied with a management team of a company in which the pension fund holds a block of shares. Stock holdings by pension funds are largely dispersed. Therefore, any intervention by pension funds in corporate governance requires the formation of a coalition of pension funds. The realization of a coordinated intervention, in turn, is subject to the problems related to the provision of public goods, such as free-riding. We find that stock dispersion among pension funds, the amount of noise traders, coordination costs and the attractiveness of the exit option are relevant factors for successful interventions. The overall probability for a successful intervention, however, is quite low.
Keywords: G23; H41; Q50; 330; Pension Funds; Public Goods; Coase Theorem; Pensionskasse; Corporate Governance; Öffentliche Güter; Theorie